The effects of N-acetylcysteine on microsomal and serum paraoxonase 1 activities at high fat diet induced obese rats - Duman, D.; Yucesan, F. Balaban; Yaman, S. Ozer; Kahraman, C.; Alver, A.; Canpolat, S.; Orem, A. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY